Optimization of Pichia pastoris Expression System for High-Level Production of Margatoxin - Naseem, Muhammad Umair; Tajti, Gabor; Gaspar, Attila; Szanto, Tibor G.; Borrego, Jesús; Panyi, Gyorgy (Frontiers in Pharmacology, 2021)
Margatoxin (MgTx) is a high-affinity blocker of voltage-gated potassium (Kv) channels. It inhibits Kv1.1–Kv1.3 ion channels in picomolar concentrations. This toxin is widely used to study physiological function of Kv ion channels in various cell types, including immune cells. Isolation of native MgTx in large quantities from scorpion venom is not affordable. Chemical synthesis and recombinant production in Escherichia coli need in vitro oxidative refolding for proper disulfide bond formation, resulting in a very low yield of peptide production. The Pichia pastoris expression system offers an economical approach to overcome all these limitations and gives a higher yield of correctly refolded recombinant peptides. In this study, improved heterologous expression of recombinant MgTx (rMgTx) in P. pastoris was obtained by using preferential codons, selecting the hyper-resistant clone against Zeocin, and optimizing the culturing conditions. About 36 ± 4 mg/L of >98% pure His-tagged rMgTx (TrMgTx) was produced, which is a threefold higher yield than has been previously reported. Proteolytic digestion of TrMgTx with factor Xa generated untagged rMgTx (UrMgTx). Both TrMgTx and UrMgTx blocked the Kv1.2 and Kv1.3 currents (patch-clamp) (Kd for Kv1.2 were 64 and 14 pM, and for Kv1.3, 86 and 50 pM, respectively) with comparable potency to the native MgTx. The analysis of the binding kinetics showed that TrMgTx had a lower association rate than UrMgTx for both Kv1.2 and Kv1.3. The dissociation rate of both the analogues was the same for Kv1.3. However, in the case of Kv1.2, TrMgTx showed a much higher dissociation rate with full recovery of the block than UrMgTx. Moreover, in a biological functional assay, both peptides significantly downregulated the expression of early activation markers IL2R and CD40L in activated CD4+ TEM lymphocytes whose activation was Kv1.3 dependent. In conclusion, the authors report that the Pichia expression system is a powerful method to produce disulfide-rich peptides, the overexpression of which could be enhanced noticeably through optimization strategies, making it more cost-effective. Since the presence of the His-tag on rMgTx only mildly altered the block equilibrium and binding kinetics, recombinant toxins could be used in ion channel research without removing the tag and could thus reduce the cost and time demand for toxin production.